Pengembangan Monitoring Suhu dan Kelembaban Berbasis Internet of Things serta Sistem Automatic Sprinkling pada Rumah Jamur - Nur Intan Ramadhan; Sulkifli Gusmin; Remigius Tandioga; Abdul Kadir Muhammad (Jurnal Sinergi Jurusan Teknik Mesin, 2022)
White oyster mushroom is one type of wood fungus that has native habitat in temperate regions with temperatures ranging from 22-28oC and humidity ranging from 60-80% RH. This mushroom cultivation can be done by storing planting media in a mushroom house (kumbung) by monitoring and maintaining the condition of temperature and humidity. At present the monitoring and maintenance of temperature and humidity is done by manually watering methods by estimating the conditions of the kumbung temperature and humidity. This causes the temperature and humidity conditions only to be estimated manually so that mushroom productivity is not maximal. This study aims to facilitate the mushroom farmers in watering and monitoring the condition of the kumbung. This system consists of sensors placed inside the cage and will detect the temperature and humidity conditions of the cage, temperature and humidity data will then be processed by the controller to enable automatic watering. watering is done with the help of a pump that is equipped with a nozzle to create a mist of water. Based on the results of observations that have been made can be obtained that the system is able to streamline time by watering automatically when the mushroom house conditions are not in accordance with the setpoint. This system is also capable of producing mushroom house conditions that can reduce temperatures to the range of 22-28o C and increase humidity to the range of 60-80% RH in less than 600 seconds. Information on monitoring the temperature and humidity of mushroom houses has been based on internet of things, which is showing the temperature and humidity conditions of mushroom houses through the website according to the data sent by the controller.